2015
DOI: 10.3892/or.2015.4155
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NADPH oxidase 4 induces apoptosis in malignant mesothelioma: Role of reactive oxygen species

Abstract: Malignant pleural mesothelioma (MPM) is an aggressive tumor that is characterized by dysregulated growth and resistance to apoptosis. Reactive oxygen species (ROS)-generating NADPH oxidase (Nox) family enzymes have been suggested to be involved in neoplastic proliferation. Both the antioxidant N-acetylcysteine (NAC) and the inhibitor of flavoprotein-dependent oxidase, diphenylene iodonium (DPI), inhibited the cell viability of MPM cells in a dose-dependent manner. To examine whether Nox-mediated ROS generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…Nox/Duox family members are regarded as major sources of ROS generation, which plays an important role in cancer development (9,16). It has been reported that inhibition of Nox activity induces apoptosis in a number of cancerous cells including pancreatic cancer, mesothelioma and sarcoma (17)(18)(19). In the present study, we demonstrated that knockdown of Nox1 but not Nox4 significantly reduced the cell viability in a subset of OSCC cell lines.…”
Section: Discussionsupporting
confidence: 58%
“…Nox/Duox family members are regarded as major sources of ROS generation, which plays an important role in cancer development (9,16). It has been reported that inhibition of Nox activity induces apoptosis in a number of cancerous cells including pancreatic cancer, mesothelioma and sarcoma (17)(18)(19). In the present study, we demonstrated that knockdown of Nox1 but not Nox4 significantly reduced the cell viability in a subset of OSCC cell lines.…”
Section: Discussionsupporting
confidence: 58%
“…Mitochondrial-localized NADPH-oxidase 4 (Nox4) also produces mROS predominantly in the form H 2 O 2 15,16 . Nox4 is implicated in the pathophysiology of numerous disease processes and its inhibition can induce mesothelioma cell apoptosis 9,17 ; however the signaling events that drive the latter process are yet undefined. In addition, monoaminoxidase (MAO), an important flavoprotein resident of the outer mitochondrial membrane, is another H 2 O 2 generator during ischemia/reperfusion injury in the brain and heart 1820 .…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, our results indicate a role for NOX-generated ROS in hypoxia-independent HIF1␣ stabilization. Preliminary findings and other studies suggest that NOX4, one of the five human NOX homologues, is of particular interest within our paradigm (58)(59)(60)(61)(62)(63)(64)(65).…”
Section: Discussionmentioning
confidence: 65%